Improvement of high load performance in gasoline compression ignition engine with PODE and multiple-injection strategy. (15th December 2018) - Liu, Jialin; Wang, Hu; Zheng, Zunqing; Li, Linpeng; Mao, Bin; Xia, Mingtao; Yao, Mingfa
Highlights: Effects of PODE and injection strategy on GCI engine are investigated at high load. Heat release acceleration ratio is proposed to describe the heat release characteristic. PODE can decrease the sensitivity of soot to the variation of injection parameters. PODE only shows advantage in soot reduction when pilot injection is employed. Low emission and PRRmax can be obtained with PODE20 and triple-injection. Abstract: The effects of PODE and multiple fuel injection strategy on combustion and emission characteristics of a multiple-cylinder gasoline compression ignition (GCI) engine are investigated at high load (BMEP = 16 bar) operation condition with a fixed engine speed of 1660 r/min. Experimental results indicate that the sensitivity of soot emission to the variation of injection parameters is decreased by blending PODE with gasoline, mainly due to the enhanced soot oxidation through PODE's high oxygen content. The main heat release of gasoline is more strongly affected by its pilot heat release compared to that of gasoline/PODE blends. Low PRRmax (maximum pressure rise rate) of about 4.5 bar/°CA can be obtained for gasoline with multiple-injection strategy, under which condition the advantage of gasoline/PODE blends only embodies in reducing soot emission, which is different from that with single injection strategy. The PHRRMI, max (maximum premixed heat release rate of main injection) and Kmain (heat release acceleration ratio of main injection) of gasoline show more sensitivity to the variation of EGR compared to that of PODE20 with pilot-main injection strategy, and the PHRRMI, max and PRRmax of gasoline increase more rapidly in contrast to that of gasoline/PODE blends as injection pressure increases. At higher injection pressure, the soot of all the fuels can be significantly decreased with penalty in PRRmax, especially for gasoline. It is seen that when PODE20 with triple-injection strategy, 1400 bar injection pressure and 30% EGR were employed under the operation condition with the engine speed of 1660 r/min and BMEP of 16 bar, the NOx of 1.3 g/kWh, soot of 0.007 g/kWh and BSFC of 199.67 g/kWh can be obtained while maintaining PRRmax of about 4.5 bar/°CA.